The effect of permissive parenting style and peer pressure on disruptive behavior: An explanatory study - Muhliawati, Yeni; Purwadi, Purwadi (Universitas Negeri Yogyakarta, 2023)
This research aims to examine the influence of permissive parenting style and peer pressure on disruptive behavior of students at Muhammadiyah 2 Yogyakarta junior high school The research method used is a quantitative-correlational method with a prediction design. The population of this research is 498 students who were registered as 7th and 8th graders in the 2021/2022 academic year. The research subjects consist of 74 students, selected using purposive sampling technique, with the criteria that they perceive their parents as permissive and have been identified to have a tendency towards disruptive behavior. The measuring instruments used consist of the disruptive behavior scale, the permissive parenting style scale, and the peer pressure scale. The analysis technique used is multiple regression. The findings of this study indicate that there is a significant simultaneous effect of permissive parenting style and peer pressure on disruptive behavior. The effective contribution produced is 42%. Permissive parenting style partially does not have an influence on disruptive behavior, while peer pressure significantly affects the occurrence of disruptive behavior. The school is recommended to increase its awareness of peer pressure that triggers disruptive behavior in students. Parents are expected to adjust their parenting style to minimize the growth of disruptive behavior in children.